2000
DOI: 10.1155/np.2000.109
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of Brain Injury‐Induced Cerebral Metabolic Depression by Amphetamine: A Cytochrome Oxidase Histochemistry Study

Abstract: Measurements of oxidative metabolic capacity following the ablation of rat sensorimotor cortex and ,he administration of amphetamine were examined to determine their effects on the metabolic dysfunction that follows brain injury. Twenty-four hours after surgery, rats sustaining either sham operations or unilateral cortical ablation were administered a single injection of D-amphetamine (2 mg/kg; i.p.) or saline and then sacrificed 24 h later. Brain tissue was processed for cytochrome oxidase histochemistry, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 82 publications
(119 reference statements)
1
12
0
Order By: Relevance
“…Several research groups have demonstrated similar long-lasting beneficial effects of amphetamine on functional recovery from brain injury in animals and Man (55)(56)(57), suggesting a common mechanism related to improvement in blood flow and facilitation of repair mechanisms.…”
Section: Discussionmentioning
confidence: 91%
“…Several research groups have demonstrated similar long-lasting beneficial effects of amphetamine on functional recovery from brain injury in animals and Man (55)(56)(57), suggesting a common mechanism related to improvement in blood flow and facilitation of repair mechanisms.…”
Section: Discussionmentioning
confidence: 91%
“…The lack of increase in BDNF in the sham-fRW group was not unexpected and is in accordance with recent studies. 18 Given the suppressive effects of glucocorticoids on BDNF, 20 it is likely that the negative effects of fRW on BDNF were related to the pronounced elevations in ACTH and CORT found with fRW. It is yet to be determined if prolonged fRW exposure would result in BDNF elevations once animals habituated to the fRW.…”
Section: Discussionmentioning
confidence: 99%
“…Stroemer et al [21] documented enhancement of neocortical neural sprouting, synaptogenesis and behavioral recovery during d-amphetamine administration in animal models. Queen and colleagues [22] and Sutton et al [23] proved that D-amphetamine counteracts reduced brain glucose metabolism in damaged sensorimotor cortex, and improves recovery from the damage. Robbins [24] emphasized that drugs affecting the central catecholaminergic (noradrenergic and dopaminergic) systems increase plasticity in the prefrontal cortex (the structure responsible for behavior planning and control), and particularly improve functions that are dependent upon the dorsolateral frontal cortex.…”
Section: Discussionmentioning
confidence: 99%